Principios de derecho laboral en las estancias de Juan Manuel de Rosas - Baroffio, Juan Francisco (2015)
We will analyze the uses and customs of rural work in the lands of the argentine dignitary Juan Manuel de Rosas, in order to identify the principles what were receipted afterwards in labor laws